Infliximab treatment of pediatric refractory Crohn’s disease: A case report - Sezin AŞIK AKMAN; Çiğdem ARIKAN; Gülben SÖZEN; Can ÖZTÜRK; Raşit Vural YAĞCI (Turkish Journal of Gastroenterology, 2019)
-